Harnessing Self-Assembly Strategies for The Rational Design of Conjugated Polymer Based Materials. - EVANS, RACHEL (My University, 2013)
Targeted control of the aggregation, morphology and optoelectronic properties of conjugated polymers is critical for the development of high performance optoelectronic devices. In this Highlight, recent advances in the use of self-assembly approaches to strategically manipulate the order, conformation and spatial distribution of conjugated polymers in various states (e.g. solution, gels, films, solids) are discussed. Emphasis is placed on the complex relationship that exists between molecular composition, self-assembly and supramolecular organisation and their consequential influence on the optoelectronic properties and device performance.
PUBLISHED
Keywords: optoelectronic properties of conjugated polymers